2006
DOI: 10.1016/s1607-551x(09)70214-1
|View full text |Cite
|
Sign up to set email alerts
|

Role Of TTF‐1, CK20, And CK7 Immunohistochemistry for Diagnosis of Primary and Secondary Lung Adenocarcinoma

Abstract: Thyroid transcription factor-1 (TTF-1), and cytokeratin 7 (CK7) and cytokeratin 20 (CK20) have recently been reported to be useful to distinguish between primary and metastatic lung adenocarcinoma. The aim of this study was to determine the usefulness of the staining patterns of pulmonary adenocarcinoma with antibodies to TTF-1, CK7, and CK20 in differentiating primary from metastatic pulmonary adenocarcinoma. Of the 66 lung adenocarcinoma specimens that were enrolled in our study, there were 40 primary lung a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 19 publications
7
78
0
2
Order By: Relevance
“…32,33 CK7 expression was significantly more frequent in pulmonary adenocarcinoma and breast adenocarcinoma than adenocarcinoma of gastrointestinal (GI) origin. 34 In our case CK7 test expressed positivity.…”
Section: -102425supporting
confidence: 47%
See 2 more Smart Citations
“…32,33 CK7 expression was significantly more frequent in pulmonary adenocarcinoma and breast adenocarcinoma than adenocarcinoma of gastrointestinal (GI) origin. 34 In our case CK7 test expressed positivity.…”
Section: -102425supporting
confidence: 47%
“…36 It is reported that CK20 expression was significantly more prevalent in adenocarcinoma that originated in the GI tract than that of pulmonary or breast origin. 34 Despite this fact, CK20 may express positivity in lung adenocarcinoma. 34,[37][38][39] Adenocarcinoma originating in the lungs is typically CK7 positive and CK20 negative.…”
Section: -102425mentioning
confidence: 99%
See 1 more Smart Citation
“…43,47 One of the genes that correlate with E2F is Ki67, still a good marker for proliferative index. 48 We obtained statistical significant higher expression of Ki67 in all patterns of adenocarcinoma, indicating active proliferative activity. 49 Another overexpressed gene in this pattern was P53 and some studies indicate that ''a low level of p53 leads to transient growth arrest and cell survival, whereas a high level promotes irreversible apoptosis'', and P53 levels may have oscillations, and it has to be explored as a target for therapy.…”
Section: Acinar Patternmentioning
confidence: 62%
“…25---32 All morphological registered patterns comprising this series of lung adenocarcinomas expressed CK7 positivity, without differences (p > 0.05), and predominant negativity for CK20, like other series published in the literature. 8,27,33,34 CK20 was expressed in 3 cases of primary lung adenocarcinoma, with expression of CK7 and TTF1.…”
Section: Discussionmentioning
confidence: 99%